Light diffusant, PC composite material and preparation method thereof

By adding newly synthesized polymethylsiloxane light diffuser to PC materials, the problem that traditional light diffusers are difficult to regulate the optical performance of PC materials is solved, and a high light transmission and high haze PC composite material is realized, which expands its application range and improves performance.

CN119859268APending Publication Date: 2025-04-22HEFEI GENIUS NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411994731.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Traditional light diffusers are difficult to meet the growing demand for optical performance regulation of PC materials, and PC materials are prone to stress cracking and not resistant to hydrolysis, which limits their application range and service life.

Method used

The polymethylsiloxane photodiffuser newly synthesized by hydrolysis-polycondensation method is used to prepare a light diffuser with appropriate particle size and uniform distribution by regulating the reactant ratio, reaction time and reaction pH value, and is used to prepare a PC composite with high light transmittance and high haze.

Benefits of technology

While ensuring high haze of PC materials, it retains a high light transmittance and the mechanical properties of the materials have not decreased significantly, expanding the application range and performance of PC composite materials in optical and other related fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005224345150000071
    Figure BDA0005224345150000071
  • Figure BDA0005224345150000081
    Figure BDA0005224345150000081
Patent Text Reader

Abstract

The invention discloses a light diffusant, a PC composite material and a preparation method of the light diffusant, and the preparation method of the light diffusant comprises the following steps: mixing methyltrimethylsiloxane, ultrapure water and a strong acid solution at 20-30 DEG C, and carrying out hydrolysis reaction to obtain a silanol solution; and S2, adding an ammonia water solution into the silanol solution obtained in the step S1, carrying out condensation polymerization for 2-2.5 hours, and filtering, washing, drying and crushing the obtained product to obtain polymethylsilsesquioxane microspheres, namely the light diffusion agent. By preparing and adding the newly synthesized polymethylsilsesquioxane light diffusant, high light transmittance is kept while high haze of the PC material is guaranteed, and the mechanical property of the material is not obviously reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to a light diffuser, a PC composite material and a preparation method thereof. Background Art

[0002] Polycarbonate (PC), as a high molecular polyester resin widely used in many fields, has many excellent properties. It has good transparency, which can meet the application scenarios with high requirements for material transparency, such as optical instruments and electronic display devices; it has excellent impact resistance, which can effectively absorb energy and maintain structural integrity when subjected to external impact; it has extremely small creep, which makes the product have good dimensional stability during long-term use; and it has excellent thermal, electrical and mechanical comprehensive properties, which makes it indispensable in many industries such as electronics, automobile manufacturing, and construction.

[0003] However, PC is not perfect. It has the defects of being prone to stress cracking and not resistant to hydrolysis. In practical applications, stress cracking may occur when subjected to external stress or internal residual stress, which not only affects the appearance of the product, but may also cause a significant decline in product performance or even failure. The property of not being resistant to hydrolysis limits the scope of use and service life of PC composite materials in humid environments or application scenarios involving contact with water.

[0004] In terms of optical applications, PC is one of the few transparent polymer materials with good processing and mechanical properties. In the past, light diffusing agents were added to the PC system to adjust its optical properties to prepare light diffusing materials. However, with the continuous development of technology and the improvement of application needs, the regulation of the optical properties of PC materials by traditional light diffusing agents has been difficult to meet the growing requirements and faces a bottleneck that is difficult to break through. Therefore, it is urgent to develop a new type of PC composite material, which can overcome the limitations of the existing technology by adding a new type of light diffusing agent, and further expand the application scope and performance of PC composite materials in optics and other related fields. This is exactly the technical problem that the present invention is committed to solving. Summary of the invention

[0005] In view of this, the present invention provides a light diffuser, a PC composite material and a preparation method thereof. By preparing and adding a newly synthesized polymethylsilsileoxane light diffuser, a high light transmittance is retained while ensuring the high haze of the PC material, and the mechanical properties of the material are not significantly reduced.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] In a first aspect, the present invention discloses a method for preparing a light diffusing agent, comprising the following steps:

[0008] S1. Mix methyltrimethylsiloxane, ultrapure water and strong acid solution at 20-30°C to produce a hydrolysis reaction to obtain a silanol solution;

[0009] S2. Adding an aqueous ammonia solution to the silanol solution obtained in step S1, polycondensation reaction is carried out for 2-2.5 hours. The obtained product is filtered, washed, dried, and crushed to obtain polymethylsilsesquioxane microspheres, i.e., a light diffuser.

[0010] As a further solution of the present invention: in step S1, the mass ratio of methyltrimethylsiloxane, ultrapure water and strong acid solution is (150-200):(100-130):(3-4); the strong acid solution is a hydrochloric acid solution, and its mass concentration is 0.001 mol / L.

[0011] As a further solution of the present invention: in order to prevent the hydrolysis reaction rate from being too fast, generating a large amount of low-crosslinked methylsiloxane and affecting the subsequent generation of light diffuser microspheres, the hydrolysis pH value should not be too small. In step S1, the hydrolysis pH value of methyltrimethylsiloxane is 5-6; the hydrolysis time of methyltrimethylsiloxane is 1-1.5h.

[0012] As a further solution of the present invention: in step S2, the mass ratio of the silanol solution to the aqueous ammonia solution is (253-334):(974-1335); the mass fraction concentration of the aqueous ammonia is 25%-28%.

[0013] As a further solution of the present invention: in order to prevent the condensation polymerization rate from being increased while not causing the reaction to be too fast and the product to gel, the pH value of the condensation polymerization should not be too high. In step S2, the pH value of the condensation polymerization reaction is 8-9.

[0014] As a further solution of the present invention: in step S2, the drying temperature is 130-150°C, and the drying time is 3-4h.

[0015] In a second aspect, the present invention discloses a light diffusing agent prepared by using the above-mentioned PC composite material.

[0016] In a third aspect, the present invention discloses a PC composite material, which is prepared by weight of 80-100 parts of PC, 1-3 parts of a light diffuser and 0.1-0.3 parts of an antioxidant, wherein the light diffuser is the light diffuser according to claim 7.

[0017] As a further solution of the present invention: the antioxidant is at least one of antioxidant 168 and antioxidant 1010.

[0018] In a fourth aspect, the present invention discloses a method for preparing the PC composite material as described above, comprising the following steps:

[0019] Mixing polycarbonate, a light diffuser and an antioxidant according to parts by weight and stirring evenly to obtain a mixture;

[0020] The mixed material is added into a twin-screw extruder for extrusion and granulation to obtain a PET composite material;

[0021] The extrusion granulation in the twin-screw extruder includes ten temperature zones arranged in sequence, and the operating temperatures are 220-240°C in zone one, 200-220°C in zone two, 210-230°C in zone three, 245-255°C in zone four, 245-255°C in zone five, 250-270°C in zone six, 250-270°C in zone seven, 255-275°C in zone eight, 255-275°C in zone nine, 255-275°C in zone ten, the die temperature is 260-280°C, and the screw speed is 350-600r / min.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The present invention adds a polymethylsilsesquioxane light diffuser newly synthesized by a hydrolysis-polycondensation method to a PC composite material. The hydrolysis-polycondensation method used for the polymethylsilsesquioxane has the advantages of mild reaction and recyclable filtrate. In addition, the hydrolysis-polycondensation method can prepare a light diffuser with a suitable particle size and uniform distribution by regulating the ratio of reactants, reaction time and reaction pH value, thereby preparing a light diffusion composite material with high light transmittance and high haze. DETAILED DESCRIPTION

[0024] For ease of understanding of the present invention, the present invention will be described more fully below in conjunction with specific embodiments. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly understood.

[0025] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0026] The specific information of the raw materials used in the following examples and comparative examples is as follows:

[0027] PC (model 02-10), Ningbo Dafeng Jiangning New Material Technology Co., Ltd.;

[0028] Methyltrimethoxysilane, Zhangjiagang Xinya Chemical Co., Ltd.;

[0029] Hydrochloric acid solution (concentration 0.001 mol / L), Taixing Meilan Chemical Co., Ltd.;

[0030] Ammonia water (mass fraction 25%-28%), Zhuzhou Dayuan Industrial Co., Ltd.;

[0031] Ultrapure water, Jiangyin Shell Chemical Co., Ltd.;

[0032] All materials are commercially available common products.

[0033] It is to be understood that the above raw materials and reagents are only examples of some specific embodiments of the present invention, so that the technical solution of the present invention is clearer, and it does not mean that the present invention can only use the above reagents, and the specific scope in the claims shall prevail. In addition, the "parts" described in the examples and comparative examples, unless otherwise specified, refer to parts by weight.

[0034] Any range described in the present invention includes the end value and any numerical value between the end values ​​and any sub-range formed by the end value or any numerical value between the end values.

[0035] Example 1

[0036] Weigh 150g of methyltrimethoxysilane, 100g of ultrapure water and 3mL of hydrochloric acid solution, add and mix, and hydrolyze at 25°C for 1h, with a stirring rate of 250r / min, and control the pH value of the system to be 5-6 during the reaction to obtain a silanol solution; mix 950mL of ultrapure water and 24mL of 26% ammonia water by mass, and then slowly add the obtained silanol solution thereto, with a stirring rate of 40r / min, and polymerize at 25°C for 2h; then filter, wash, and dry at 150°C, and grind in a ball mill to obtain polymethylsilsesquioxane microspheres, i.e., a light diffuser.

[0037] 100 parts of PC, 0.3 parts of light diffuser and 0.1 parts of antioxidant 1010 were weighed, mixed and stirred evenly to obtain a mixture; the obtained mixture was added into a twin-screw extruder for extrusion and granulation to obtain a PC composite material, which was recorded as A1.

[0038] Among them, the working temperature and screw speed of each zone of the twin-screw extruder are 220℃ for zone 1, 200℃ for zone 2, 210℃ for zone 3, 245℃ for zone 4, 245℃ for zone 5, 250℃ for zone 6, 250℃ for zone 7, 255℃ for zone 8, 255℃ for zone 9, 255℃ for zone 10, the head temperature is 255℃, and the screw speed is 350r / min.

[0039] Example 2

[0040] Weigh 200g of methyltrimethoxysilane, 130g of ultrapure water and 4mL of hydrochloric acid solution, add and mix, and hydrolyze at 25°C for 1.5h, with a stirring rate of 300r / min, and control the pH value of the system to be 5-6 during the reaction to obtain a silanol solution; mix 1300mL of ultrapure water and 35mL of 26% ammonia water by mass, and then slowly add the obtained silanol solution thereto, with a stirring rate of 50r / min, and polymerize at 25°C for 2.5h; then filter, wash, dry at 130°C, and grind in a ball mill to obtain polymethylsilsesquioxane microspheres, i.e., a light diffuser.

[0041] 100 parts of PC, 0.5 parts of light diffuser and 0.1 parts of antioxidant 1010 were weighed, mixed and stirred evenly to obtain a mixture; the obtained mixture was added into a twin-screw extruder for extrusion and granulation to obtain a PC composite material, which was recorded as A2.

[0042] Among them, the working temperature and screw speed of each zone of the twin-screw extruder are 230℃ for zone 1, 210℃ for zone 2, 220℃ for zone 3, 245℃ for zone 4, 245℃ for zone 5, 250℃ for zone 6, 250℃ for zone 7, 260℃ for zone 8, 260℃ for zone 9, 260℃ for zone 10, the head temperature is 260℃, and the screw speed is 350r / min.

[0043] Example 3

[0044] Weigh 170g of methyltrimethoxysilane, 110g of ultrapure water and 3.4mL of hydrochloric acid solution, add and mix, and hydrolyze at 25°C for 1h, with a stirring rate of 280r / min, and control the pH value of the system to be 5-6 during the reaction to obtain a silanol solution; mix 1100mL of ultrapure water and 30mL of 26% ammonia water by mass, and then slowly add the obtained silanol solution thereto, with a stirring rate of 50r / min, and polymerize at 25°C for 2h; then filter, wash, and dry at 150°C, and grind in a ball mill to obtain polymethylsilsesquioxane microspheres, i.e., a light diffuser.

[0045] 100 parts of PC, 0.8 parts of light diffuser and 0.1 parts of antioxidant 1010 were weighed, mixed and stirred to obtain a mixture; the obtained mixture was added to a twin-screw extruder for extrusion and granulation to obtain a PC composite material, which was recorded as A3. The working temperature and screw speed of each zone of the twin-screw extruder were 235°C for zone 1, 215°C for zone 2, 230°C for zone 3, 245°C for zone 4, 245°C for zone 5, 250°C for zone 6, 250°C for zone 7, 255°C for zone 8, 255°C for zone 9, 260°C for zone 10, the die temperature was 260°C, and the screw speed was 400r / min.

[0046] Comparative Example 1

[0047] 100 parts of PC and 0.1 parts of antioxidant 1010 were weighed, mixed and stirred to obtain a mixture; the obtained mixture was added to a twin-screw extruder for extrusion and granulation to obtain a PC composite material, which was recorded as D1. The working temperature and screw speed of each zone of the twin-screw extruder were 220°C for zone 1, 200°C for zone 2, 210°C for zone 3, 245°C for zone 4, 245°C for zone 5, 250°C for zone 6, 250°C for zone 7, 255°C for zone 8, 255°C for zone 9, and 255°C for zone 10, the die head temperature was 255°C, and the screw speed was 350r / min.

[0048] Comparative Example 2

[0049] 100 parts of PC, 0.5 parts of light diffuser 7056A and 0.1 parts of antioxidant 1010 were weighed, mixed and stirred evenly to obtain a mixture; the obtained mixture was added into a twin-screw extruder for extrusion and granulation to obtain a PC composite material, which was recorded as D2.

[0050] Among them, the working temperature and screw speed of each zone of the twin-screw extruder are 230℃ for zone 1, 210℃ for zone 2, 220℃ for zone 3, 245℃ for zone 4, 245℃ for zone 5, 250℃ for zone 6, 250℃ for zone 7, 260℃ for zone 8, 260℃ for zone 9, 260℃ for zone 10, the head temperature is 260℃, and the screw speed is 350r / min.

[0051] Comparative Example 3

[0052] 100 parts of PC, 0.5 parts of light diffuser kmp-590 and 0.1 parts of antioxidant 1010 were weighed, mixed and stirred evenly to obtain a mixture; the obtained mixture was added into a twin-screw extruder for extrusion and granulation to obtain a PC composite material, which was recorded as D3.

[0053] Among them, the working temperature and screw speed of each zone of the twin-screw extruder are 235℃ for zone 1, 215℃ for zone 2, 230℃ for zone 3, 245℃ for zone 4, 245℃ for zone 5, 250℃ for zone 6, 250℃ for zone 7, 255℃ for zone 8, 255℃ for zone 9, 260℃ for zone 10, the head temperature is 260℃, and the screw speed is 400r / min.

[0054] Comparative Example 4

[0055] 100 parts of PC, 0.5 parts of acrylic light diffuser EXM-5 and 0.1 parts of antioxidant 1010 were weighed, mixed and stirred evenly to obtain a mixture; the obtained mixture was added into a twin-screw extruder for extrusion and granulation to obtain a PC composite material, which was recorded as D4.

[0056] Among them, the working temperature and screw speed of each zone of the twin-screw extruder are 235℃ for zone 1, 215℃ for zone 2, 230℃ for zone 3, 245℃ for zone 4, 245℃ for zone 5, 250℃ for zone 6, 250℃ for zone 7, 255℃ for zone 8, 255℃ for zone 9, 260℃ for zone 10, the head temperature is 260℃, and the screw speed is 400r / min.

[0057] Comparative Example 5

[0058] 100 parts of PC, 0.5 parts of inorganic light diffuser BF-N and 0.1 parts of antioxidant 1010 were weighed, mixed and stirred evenly to obtain a mixture; the obtained mixture was added into a twin-screw extruder for extrusion and granulation to obtain a PC composite material, which was recorded as D5.

[0059] Among them, the working temperature and screw speed of each zone of the twin-screw extruder are 235℃ for zone 1, 215℃ for zone 2, 230℃ for zone 3, 245℃ for zone 4, 245℃ for zone 5, 250℃ for zone 6, 250℃ for zone 7, 255℃ for zone 8, 255℃ for zone 9, 260℃ for zone 10, the head temperature is 260℃, and the screw speed is 400r / min.

[0060] Comparative Example 6

[0061] Weigh 150g of methyltrimethoxysilane, 100g of ultrapure water and 3mL of hydrochloric acid solution, add and mix, and hydrolyze at 25°C for 1h, with a stirring rate of 250r / min, and control the pH value of the system to be 4-5 during the reaction to obtain a silanol solution; mix 950mL of ultrapure water and 24mL of 26% ammonia water by mass, and then slowly add the obtained silanol solution thereto, with a stirring rate of 40r / min, and polymerize at 25°C for 2h; then filter, wash, dry at 150°C, and grind in a ball mill to obtain polymethylsilsesquioxane microspheres, i.e., a light diffuser.

[0062] 100 parts of PC, 0.3 parts of light diffuser and 0.1 parts of antioxidant 1010 were weighed, mixed and stirred evenly to obtain a mixture; the obtained mixture was added into a twin-screw extruder for extrusion and granulation to obtain a PC composite material, which was recorded as D6.

[0063] Among them, the working temperature and screw speed of each zone of the twin-screw extruder are 220℃ for zone 1, 200℃ for zone 2, 210℃ for zone 3, 245℃ for zone 4, 245℃ for zone 5, 250℃ for zone 6, 250℃ for zone 7, 255℃ for zone 8, 255℃ for zone 9, 255℃ for zone 10, the head temperature is 255℃, and the screw speed is 350r / min.

[0064] Comparative Example 7

[0065] Weigh 150g of methyltrimethoxysilane, 100g of ultrapure water and 3mL of hydrochloric acid solution, add and mix, and hydrolyze at 25°C for 1h, with a stirring rate of 250r / min, and control the pH value of the system to be 3-4 during the reaction to obtain a silanol solution; mix 950mL of ultrapure water and 24mL of 26% ammonia water by mass, and then slowly add the obtained silanol solution thereto, with a stirring rate of 40r / min, and polymerize at 25°C for 2h; then filter, wash, and dry at 150°C, and grind in a ball mill to obtain polymethylsilsesquioxane microspheres, i.e., a light diffuser.

[0066] 100 parts of PC, 0.3 parts of light diffuser and 0.1 parts of antioxidant 1010 were weighed, mixed and stirred evenly to obtain a mixture; the obtained mixture was added into a twin-screw extruder for extrusion and granulation to obtain a PC composite material, which was recorded as D7.

[0067] Among them, the working temperature and screw speed of each zone of the twin-screw extruder are 220℃ for zone 1, 200℃ for zone 2, 210℃ for zone 3, 245℃ for zone 4, 245℃ for zone 5, 250℃ for zone 6, 250℃ for zone 7, 255℃ for zone 8, 255℃ for zone 9, 255℃ for zone 10, the head temperature is 255℃, and the screw speed is 350r / min.

[0068] The PC composite materials prepared in the embodiments and comparative examples were subjected to relevant performance tests, wherein the test standards for light transmittance and haze refer to ISO 14782:2009, and test pieces with specifications of (100 mm ± 2 mm) × (50 mm ± 2 mm) × (3 mm ± 0.1 mm) are used; the tensile strength and elongation at break tests refer to ISO 527-1:2019 standard; the flexural strength and flexural modulus tests refer to ISO 178:2019 standard; the simply supported beam notched impact strength test refers to ISO 179-1:2010 standard; the Vicat softening temperature test refers to ISO 306:2013 standard; the test results are shown in Table 1.

[0069] Table 1

[0070]

[0071]

[0072] It can be seen from the test results in Table 1 that, in general, the performance of Example 1 is better. While ensuring high haze, it also retains a high light transmittance, and the mechanical properties of the material have no obvious decrease. From Comparative Examples D2 and D3, it can be seen that the method used in the present invention has a higher light transmittance and higher thermal stability under the same addition amount for both being silicone light diffusers. From Comparative Example D4, it can be seen that compared with acrylic light diffusers, the method used in the present invention has a higher haze without affecting the thermal stability of the material under the same addition amount. From Comparative Example D5, it can be seen that the method used in the present invention can effectively improve the haze of the material under the same addition amount. From Comparative Examples D6 and D7, it can be seen that the method used in the present invention, under the same addition amount, as the hydrolysis pH value decreases during the preparation of the light diffuser, the haze of the composite material gradually decreases and the transmittance gradually increases. This is because in a low pH environment, the hydrolysis rate is too fast, resulting in the generation of a large amount of methyl polysiloxane crosslinks, and the particle size of the light diffusion microspheres increases, resulting in a decrease in the haze of the light diffuser plate and an increase in the light transmittance. At the same time, large particle size of light diffusers also reduces the tensile strength and impact resistance of the composite materials.

[0073] Although this specification is described according to implementation modes, not every implementation mode includes only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

[0074] Therefore, the above description is only a preferred embodiment of the present application and is not intended to limit the scope of implementation of the present application; that is, all equivalent changes made according to the scope of the claims of the present application are within the protection scope of the claims of the present application.

Claims

1. A method for preparing a light diffusing agent, characterized in that: The following steps are involved: S1. Mix methyltrimethylsiloxane, ultrapure water and strong acid solution at 20-30°C to produce a hydrolysis reaction to obtain a silanol solution; S2. Adding an aqueous ammonia solution to the silanol solution obtained in step S1, polycondensation reaction is carried out for 2-2.5 hours. The obtained product is filtered, washed, dried, and crushed to obtain polymethylsilsesquioxane microspheres, i.e., a light diffuser.

2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of methyltrimethylsiloxane, ultrapure water and strong acid solution is (150-200): (100-130): (3-4); The strong acid solution is a hydrochloric acid solution, and its mass concentration is 0.001 mol / L.

3. The preparation method according to claim 1, characterized in that: In order to prevent the hydrolysis reaction rate from being too fast, generating a large amount of low-crosslinked methylsiloxane and affecting the subsequent generation of light diffuser microspheres, the hydrolysis pH value should not be too small. In step S1, the hydrolysis pH value of methyltrimethylsiloxane is 5-6; the hydrolysis time of methyltrimethylsiloxane is 1-1.5h.

4. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the silanol solution to the aqueous ammonia solution is (253-334):(974-1335); the mass fraction concentration of the aqueous ammonia is 25%-28%.

5. The preparation method according to claim 1, characterized in that: In order to prevent the condensation rate from being increased and the product from gelling due to the too fast reaction, the pH value of the condensation reaction should not be too high. In step S2, the pH value of the condensation reaction is 8-9.

6. The preparation method according to claim 1, characterized in that: In step S2, the drying temperature is 130-150°C and the drying time is 3-4h.

7. A light diffuser prepared using the PC composite material according to any one of claims 1 to 8.

8. A PC composite material, characterized in that: The invention is prepared from 80-100 parts of PC, 1-3 parts of light diffuser and 0.1-0.3 parts of antioxidant in parts by weight, wherein the light diffuser is the light diffuser according to claim 7.

9. The PC composite material according to claim 8, characterized in that: The antioxidant is at least one of the antioxidant 168 and the antioxidant 1010 .

10. A method for preparing the PC composite material according to any one of claims 8 to 9, characterized in that: The following steps are involved: Mixing polycarbonate, a light diffuser and an antioxidant according to parts by weight and stirring evenly to obtain a mixture; The mixed material is added into a twin-screw extruder for extrusion and granulation to obtain a PET composite material; The extrusion granulation in the twin-screw extruder includes ten temperature zones arranged in sequence, and the operating temperatures are 220-240°C in zone one, 200-220°C in zone two, 210-230°C in zone three, 245-255°C in zone four, 245-255°C in zone five, 250-270°C in zone six, 250-270°C in zone seven, 255-275°C in zone eight, 255-275°C in zone nine, 255-275°C in zone ten, the die temperature is 260-280°C, and the screw speed is 350-600r / min.